Smoking Cessation With 20 Hz Repetitive Transcranial Magnetic Stimulation (rTMS) Applied to Two Brain Regions: A Pilot Study - Chang, Da; Zhang, Jian; Peng, Wei; Shen, Zhuowen; Gao, Xin; Du, Youhong; Ge, Qiu; Song, Donghui; Shang, Yuanqi; Wang, Ze (Frontiers in Human Neuroscience, 2018)
Chronic smoking impairs brain functions in prefrontal cortex and the projecting meso-cortical limbic system. The purpose of this pilot study is to examine whether modulating frontal brain activity using high-frequency repetitive transcranial magnetic stimulation (rTMS) can improve smoking cessation and to explore the changing pattern of the brain activity after treatment. 14 treatment-seeking smokers were offered a program of 10 days rTMS treatment and followed up for 25 more days. 20 Hz rTMS was sequentially applied on the left dorso-lateral prefrontal cortex (DLPFC) and the superior medial frontal cortex (SMFC). Carbon monoxide (CO) level, withdrawal, craving scales and neuroimaging data were collected. 10 smokers finished the entire treatment program, 90% of them didn’t smoke during the 25 days follow-up time. Significant smoking craving reduction and resting brain activity reduction measured by cerebral blood flow (CBF) and brain entropy (BEN) were observed after 10 days 20 Hz rTMS treatments compared to baseline. While limited by sample size, these pilot findings definitely showed a high potential of multiple-target high-frequency rTMS in smoking cessation and the utility of fMRI for objectively assessing the treatment effects.